Watchtowers, Mastic Contraband and Rural Communities in the Aegean Archipelago under Ottoman Sovereignty - Ierapetritis, Dimitrios G. (The Historical Review/La Revue Historique, 2013)
The construction of watchtowers on the islands of the Aegean Archipelago was common practice for Western peoples in the context of a systematic effort to provide military protection for agricultural areas and the populations of their rich commercial colonies. After the weakening of these colonies and the arrival of the Ottomans, the watchtowers, known as viglae, continued to operate, as they were closely associated with the socio-economic, everyday life of the region’s residents. Using the case study of the community of 21 mastic-gathering villages (Mastihohoria) of south Chios, this article aims to: a) investigate the main and secondary objectives of the Ottoman administration in maintaining the operation of the viglae; b) study the system of operation of the viglae during the period of Ottoman rule; and c) explore the maintenance of viglae during this era. This article is based on qualitative research, as it studies documents found primarily in archival material, such as notarial acts, communal decisions, and correspondence between members of the Ottoman administration and community representatives, as well as other historical, travel and geographical resources